Temporal and spatial effects on maize-bean row intercropping - Flesch, Roger Delmar (Pesquisa Agropecuaria Brasileira, 2002)
Maize (Zea mays L.) planting dates and spatial arrangements between maize (cv. Pioneer 6872) and common bean (Phaseolus vulgaris L. cv. Rio Tibagi) in a row intercropping system was conducted in Chapecó, SC, Brazil, to determine the best agronomic combinations and the economically most efficient intercropping system. Five experiments were carried out annually and consisted of five maize planting dates in relation to bean, with four spatial arrangements for each planting date. The experimental design was randomized complete blocks with four replications of each treatment. Maize was planted 15 days before bean, simultaneously to bean, and 15, 30 and 45 days after bean planting. The spatial arrangements were 1M:1B (one maize row alternated with one bean row), 2M:2B, 2M:3B and 1M:2B. Planting dates and spatial arrangements influenced the yields of maize and common bean. The most efficient spatial arrangements for maize were 1M:1B and 2M:2B and for common bean were 1M:2B and 2M:3B. Early planting of common bean by 15 days over maize increased its yield by 35% while the maize yield was reduced by 7.5%. Agronomic and economic efficiency of row intercropping over sole cropping increased with common bean early planting.